Faktor Pendorong Dan Penarik Penduduk Migran Kota Bekasi Ke Jakarta - Subhan Adi A; Nanik Istiyani; Andjar Widjajanti (UPT Penerbitan Universitas Jember, 2017)
This study aims to identification factors Bekasi City's migrants peoples to Jakarta. Population in this research was all themigrant peoples in Bekasi City and whose doing sekuler/commuter mobility were the samples. The analytical method used inthis research is qualitative descriptive. The results from this study are: (1) push factors that driving migrants to Jakarta Bekasicity are education, economic, and transportation, and (2) its pull factor are education, economy (job oppurtunity and incomerate are higher), health, and entertainment.